2014
DOI: 10.1165/rcmb.2013-0342oc
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Interleukin-13 with Tralokinumab Attenuates Lung Fibrosis and Epithelial Damage in a Humanized SCID Idiopathic Pulmonary Fibrosis Model

Abstract: The aberrant fibrotic and repair responses in the lung are major hallmarks of idiopathic pulmonary fibrosis (IPF). Numerous antifibrotic strategies have been used in the clinic with limited success, raising the possibility that an effective therapeutic strategy in this disease must inhibit fibrosis and promote appropriate lung repair mechanisms. IL-13 represents an attractive target in IPF, but its disease association and mechanism of action remains unknown. In the present study, an overexpression of IL-13 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(84 citation statements)
references
References 46 publications
1
83
0
Order By: Relevance
“…As shown in Figure 8C, these studies highlight a modest IL-13Rα2 signal in lungs from normal individuals, most of which was intracellular. In keeping with the literature (32,33), an enhanced IL-13Rα2 signal, some of which was localized to cell membranes, was seen in the samples from the IPF patients ( Figure 8C). In contrast, in HPS lungs IL-13Rα2 was expressed at lower levels, and the cytoplasmic pool was readily noted but the membrane pool could not be detected ( Figure 8C).…”
Section: 4supporting
confidence: 89%
“…As shown in Figure 8C, these studies highlight a modest IL-13Rα2 signal in lungs from normal individuals, most of which was intracellular. In keeping with the literature (32,33), an enhanced IL-13Rα2 signal, some of which was localized to cell membranes, was seen in the samples from the IPF patients ( Figure 8C). In contrast, in HPS lungs IL-13Rα2 was expressed at lower levels, and the cytoplasmic pool was readily noted but the membrane pool could not be detected ( Figure 8C).…”
Section: 4supporting
confidence: 89%
“…They found that IL-13R␣2 deficiency resulted in decreased survival, increased granuloma size, and increased liver fibrosis (19). Recently, Murray et al have elegantly demonstrated that targeting IL-13 directly with tralokinumab also attenuates fibrosis and epithelial damage, highlighting the importance of targeting this ligand/receptor complex (21).…”
Section: Discussionmentioning
confidence: 99%
“…Usually, it promotes IgE class switching and inhibits inflammatory cytokine production, and, more recently, it was discovered that IL-13 is a regulator of the ECM and plays a role in inducing tissue fibrosis in schistosomiasis and asthma. Its overexpression has a direct pro-fibrotic action in animal models [95] and, on the other hand, its downregulation inhibits the development of fibrosis [96,97]. Wilson and Wynn [98] demonstrated that an elevation in IL-13 level is involved in lung fibrosis, and several studies showed higher levels of this cytokine in lungs of IPF patients [99,100].…”
Section: Immune Dysregulation and Inflammationmentioning
confidence: 99%
“…Wilson and Wynn [98] demonstrated that an elevation in IL-13 level is involved in lung fibrosis, and several studies showed higher levels of this cytokine in lungs of IPF patients [99,100]. These findings correlate directly with the rate of disease progression [97] and inversely with percent predicted FVC and D LCO [100]. IL-13 pro-fibrotic activity works in synergy with IL-4 [96], but its role is controversial.…”
Section: Immune Dysregulation and Inflammationmentioning
confidence: 99%